2021
DOI: 10.1177/00914150211050882
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Support, Help-Seeking Attitudes and Help-Seeking Intentions on Older Australians’ use of Mental Health Services for Depression and Anxiety Symptoms

Abstract: This study investigated the influence of predisposing factors (social support, help-seeking attitudes and help-seeking intentions) on older Australian adults’ use of mental health services for depression and/or anxiety symptoms. Participants were 214 older Australian adults (61% female; aged between 60 and 96 years; M  =  75.15 years, SD  =  8.40 years) who completed a self-report questionnaire that measured predisposing factors and lifetime mental health service use for depression and/or anxiety symptoms. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In our study, social support increased the likelihood of favorable attitudes towards seeking psychological help. Social support has been previously identified as an important enabler of positive mental health seeking attitudes among older adults [ 26 , 72 ]. An Australian study found that older adults with depression or anxiety symptoms who had a social support network, were more likely to be encouraged to seek mental health care [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, social support increased the likelihood of favorable attitudes towards seeking psychological help. Social support has been previously identified as an important enabler of positive mental health seeking attitudes among older adults [ 26 , 72 ]. An Australian study found that older adults with depression or anxiety symptoms who had a social support network, were more likely to be encouraged to seek mental health care [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows that, during the COVID-19 pandemic, social support has been negatively correlated with anxiety, whereas good social support will help reduce anxiety (Ao et al, 2020). Older adults with higher levels of social support use fewer mental health services for anxiety (Bretherton, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Severe degree of social stigma: score of 93 to 111. Tool III: Older adults' health seeking behaviors structured interview schedule: This tool is a 17 items that developed by the researchers after reviewing the related literatures (Bretherton, 2021;Noorrizki et al, 2021) to assess the health seeking behaviors among older adults. It required the older adult to indicate the extent to which they agree or disagree with each health behaviors on a 3-point Likert scale, scoring from disagree (1), slightly agree (2), strongly agree (3).…”
Section: Toolmentioning
confidence: 99%